Research on the Design of Cultural and Creative Products in Southern Fujian Based on Narrative Design Methods. (November 2020) - Zhou, Xiaoping; Lian, Xiaobo; Guo, Huiting
Abstract: Narrative design method is an important form of cultural creative design. An important manifestation of the combination of traditional culture and modern culture is cultural creative products. Southern Fujian cultural elements are unique and have an important position in Chinese culture. Combining southern Fujian cultural elements with modernity and carrying out cultural and creative design will help promote the innovative development of traditional Chinese culture. Based on this, this article analyzes Minnan cultural and creative products.